Gastric type adenocarcinoma of the cervix presenting as ovarian neoplasm - Jamie L. McDowell; Nicole Joseph; Pallvi K. Singh; Hong Yin; Scott C. Purinton (Elsevier, 2021)
Gastric-type adenocarcinoma of the uterine cervix (GAS) is a rare subtype of mucinous adenocarcinoma, unrelated to HPV infection. It first appeared in the World Health Organization Classification of Tumours of Female Reproductive Organs in 2014.This report discusses a 50-year-old, Caucasian female who presented with new onset abdominal pain, distension, and diffuse ascites. CT scan revealed an ovarian neoplasm later diagnosed as GAS on surgical pathology. Immunohistological stains were positive for PAX8, CK7, CK20 (focally strong), CAIX (strong), CEA (patchy), MUC6 (strong), HNF1b, UBC, RNA, KOC (focal), and P53 (wild type). Tumor cells were negative for p16, PAX2, ER, low-risk 5 HPV, high-risk 18 HPV, and CDX2. The proliferative index (Ki-67) was 20%. The patient is scheduled to receive systemic chemotherapy of cisplatin, paclitaxel, and bevacizumab. Following chemotherapy, she will undergo external beam radiation and vaginal brachytherapy.The prevalence of GAS in the United States is currently unknown. Little is understood about the ideal treatment for this disease, and prognosis is very poor. As more cases are identified and reported, more targeted therapy be developed and trialed in these patients.